2018
DOI: 10.15869/itobiad.405334
|View full text |Cite
|
Sign up to set email alerts
|

Yükseköğretim Kurumlarında Memnuniyet Kavramı: Kuramsal Bir Derleme

Abstract: Bu çalışmanın amacı, memnuniyet kavramının ve bu kavramla ilişkili faktörlerin yükseköğretim kurumları bakımından kapsamlı biçimde irdelenmesidir. Bu amacı gerçekleştirebilmek üzere yükseköğretim kurumlarının paydaşlarının belirlenmesi, memnuniyete etki eden faktörlerin ortaya konması ve farklı bilim dallarında araştırma konusu olan müşteri memnuniyeti, hizmet kalitesi, kurumsal imaj, kurumsal itibar ve paydaş kavramlarının yükseköğretim kurumlarına uyarlanabilir oluşunun ilgili ulusal ve uluslararası yazına d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…After higher education, every graduate aims to reach economically strong opportunities (Illich, 2013). It is observed that higher education institutions that are open to sharing knowledge and experience cooperate with the industry in order to provide students with the qualifications required by the profession (Yüksel et al, 2018). Studies have shown that the expectation of high income, access to new job opportunities, gaining status and prestige are effective in university and department preferences in our country (Çakır, 2007;Yıldız et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…After higher education, every graduate aims to reach economically strong opportunities (Illich, 2013). It is observed that higher education institutions that are open to sharing knowledge and experience cooperate with the industry in order to provide students with the qualifications required by the profession (Yüksel et al, 2018). Studies have shown that the expectation of high income, access to new job opportunities, gaining status and prestige are effective in university and department preferences in our country (Çakır, 2007;Yıldız et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Üniversiteler, sadece öğrencilere meslek kazandırmakla kalmamakta, aynı zamanda öğrencilerin yaşam biçimlerine de yön vermektedirler (Baskan, 2001). Toplumsal hayatta bu denli önemli rol oynayan üniversitelerinin temel performans göstergesi öğrencileri ne ölçüde memnun ettiğidir (Yüksel, Bilgen ve Kobal, 2018).…”
Section: şEkil 1 üNiversite çıKtıları Ve Beklenen Ekonomik Etkilerunclassified